Analysis of precipitation time characteristics in key water demand period of main crops in Western Guanzhong. Issue 6 (March 2020) - Qu, Tong; Xia, Cong; Huang, Lingmei
Abstract: Based on the daily precipitation data of seven meteorological stations in the western part of Guanzhong area from 1970 to 2016, the time characteristics of precipitation series are analysed by using the methods of sliding t-test, wavelet analysis and R/S. The results showed that the annual precipitation, summer maize and winter wheat precipitation in the key water demand period generally showed no significant downward trend, and there is no significant mutation point. It will maintain the change characteristics consistent with the recent historical period in the future, which provides certain reference for the regional water resources planning and reasonable allocation, agricultural planting structure adjustment, and irrigation system improvement.